2020
DOI: 10.1007/s00330-020-07504-2
|View full text |Cite
|
Sign up to set email alerts
|

Which role for chest x-ray score in predicting the outcome in COVID-19 pneumonia?

Abstract: Objective We aim to demonstrate that a chest X-ray (CXR) scoring system for COVID-19 patients correlates with patient outcome and has a prognostic value. Methods This retrospective study included CXRs of COVID-19 patients that reported the Brixia score, a semi-quantitative scoring system rating lung involvement from 0 to 18. The highest (H) and lowest (L) values were registered along with scores on admission (A) and end of hospitalization (E). The Brixia score was correlated with the outcome (death or dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 12 publications
1
52
0
5
Order By: Relevance
“…There has been recent interest in the potential of scoring radiographic severity of SARS-CoV-2 pneumonitis changes to predict important patient outcomes. A number of studies report such data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our study focusses on percentage opacification, a simple and readily applicable scoring system, comparing it directly to BRIXIA and RALE scores that have been studied more extensively.…”
Section: N P R E S Smentioning
confidence: 99%
See 3 more Smart Citations
“…There has been recent interest in the potential of scoring radiographic severity of SARS-CoV-2 pneumonitis changes to predict important patient outcomes. A number of studies report such data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our study focusses on percentage opacification, a simple and readily applicable scoring system, comparing it directly to BRIXIA and RALE scores that have been studied more extensively.…”
Section: N P R E S Smentioning
confidence: 99%
“…Two other studies have also examined the impact of radiological severity scoring systems in predicting patient outcome. Maroldi et al [12] examined the BRIXIA score in a cohort of similar size. That study incorporated radiographic scoring for I n p r e s s radiographs taken during the patients' SARS-CoV-2 admission to determine if the BRIXIA score could predict outcomes.…”
Section: N P R E S Smentioning
confidence: 99%
See 2 more Smart Citations
“… 23 A worsening Brixia score and a Brixia score of >3 on admission are correlated with disease severity and death. 24 Feng, et al 25 found that age, neutrophil-lymphocyte ratio, and chest computed tomography severity score corresponded with severe pneumonia in COVID-19, and developed a nomogram on the risk of severe pneumonia. Given its predictor of severity and mortality, chest X-rays were nonspecific, but low in cost and easy available.…”
Section: Discussionmentioning
confidence: 99%